The vaginal microbiota, human papillomavirus infection and cervical intraepithelial neoplasia: what do we know and where are we going next?. Issue 1 (December 2016) - Mitra, Anita; MacIntyre, David; Marchesi, Julian; Lee, Yun; Bennett, Phillip; Kyrgiou, Maria
Abstract The vaginal microbiota plays a significant role in health and disease of the female reproductive tract. Next-generation sequencing techniques based upon the analysis of bacterial 16S rRNA genes permit in-depth study of vaginal microbial community structure to a level of detail not possible with standard culture-based microbiological techniques. The human papillomavirus (HPV) causes both cervical intraepithelial neoplasia (CIN) and cervical cancer. Although the virus is highly prevalent, only a small number of women have a persistent HPV infection and subsequently develop clinically significant disease. There is emerging evidence which leads us to conclude that increased diversity of vaginal microbiota combined with reduced relative abundance ofLactobacillus spp. is involved in HPV acquisition and persistence and the development of cervical precancer and cancer. In this review, we summarise the current literature and discuss potential mechanisms for the involvement of vaginal microbiota in the evolution of CIN and cervical cancer. The concept of manipulation of vaginal bacterial communities using pre- and probiotics is also discussed as an exciting prospect for the field of cervical pathology.